2011
DOI: 10.4209/aaqr.2011.04.0038
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Characteristics of nano-TiO2 Aerosol in the Workplace

Abstract: In this study, the distribution characteristics of nano-TiO 2 aerosol have been studied to get insight of the suspension, agglomeration and depositing performances of aerosol nanoparticles in the workplace. The number concentration and mass concentration of the aerosols have been characterized by using a wide-range particle spectrometer and cascade impactor samplers, respectively. Water based wet aerosol samplers, as well as its corresponding analysis approaches based on ultraviolet spectrometry, have also bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Many in vitro and in vivo studies use coatings, such as surfactants, in order to mimic the lung lining fluid in an in vivo scenario [ 44 ] and/or to obtain monodisperse, stabilized suspensions [ 45 ]. Here, we did not use coatings because: 1) real world RT exposures do not involve monodispersed NPs [ 46 ]; 2) upon deposition into the lung, particles will interact with lung lining fluid and become coated with proteins and other biomolecules; 3) regardless of the suspension coating or dispersion at the time of exposure, particles may agglomerate within the lung upon deposition [ 47 ]; 4) we wanted to keep the material as pristine as possible for better comparison to the uncoated, pristine material used for inhalation; and, 5) in a pilot study, we determined that pretreatments with coating or sonication can modify the inflammatory response (Additional file 1 : Figure S1). We found that pretreatment with dispersion medium (DM; 1,2-dipalmitoyl-sn-glycero-3-phosphocholine + albumin in saline [ 48 ]) resulted in significantly lower neutrophil influx than with saline alone (Additional file 1 : Figure S1A).…”
Section: Resultsmentioning
confidence: 99%
“…Many in vitro and in vivo studies use coatings, such as surfactants, in order to mimic the lung lining fluid in an in vivo scenario [ 44 ] and/or to obtain monodisperse, stabilized suspensions [ 45 ]. Here, we did not use coatings because: 1) real world RT exposures do not involve monodispersed NPs [ 46 ]; 2) upon deposition into the lung, particles will interact with lung lining fluid and become coated with proteins and other biomolecules; 3) regardless of the suspension coating or dispersion at the time of exposure, particles may agglomerate within the lung upon deposition [ 47 ]; 4) we wanted to keep the material as pristine as possible for better comparison to the uncoated, pristine material used for inhalation; and, 5) in a pilot study, we determined that pretreatments with coating or sonication can modify the inflammatory response (Additional file 1 : Figure S1). We found that pretreatment with dispersion medium (DM; 1,2-dipalmitoyl-sn-glycero-3-phosphocholine + albumin in saline [ 48 ]) resulted in significantly lower neutrophil influx than with saline alone (Additional file 1 : Figure S1A).…”
Section: Resultsmentioning
confidence: 99%
“…In nanoparticle research, especially titanium dioxide is under scrutiny. Though there is currently no epidemiologic proof for a dose-response relation between ultrafine TiO 2 and lung cancer in TiO 2 -exposed workers, animal studies (rats) have shown dose-response relationships for ultrafine TiO 2 and cancerous, as well as inflammatory endpoints [40][41][42]. Therefore, more information about ultrafine toxicity and effective preventive means are needed to reduce health threats at the workplace.…”
Section: Discussionmentioning
confidence: 99%
“…However, instruments capable of measuring aerosol surface areas in the field are not widely available. In addition, only a few research efforts are focused on the study of particle number concentrations (Tsang et al, 2008;Hussein et al, 2011;Yang et al, 2011). By measuring the number concentration distribution of aerosols in the workshop and the diameter of the primary particles, it is easy to display the agglomeration status of the aerosol particles, and to convert to the other two characteristics of the aerosol; i.e., the mass concentration and the surface area concentration.…”
Section: Introductionmentioning
confidence: 99%